Fostering Professional Competencies in Engineering Undergraduates with EPS@ISEP - Benedita Malheiro; Pedro Guedes; Manuel F. Silva; Paulo Ferreira (MDPI AG, 2019)
Engineering education addresses the development of professional competencies in undergraduates. In this context, the core set of professional competencies includes critical thinking and problem solving, effective communication, collaboration and team building, and creativity and innovation—also known as the four Cs—as well as socio-professional ethics and sustainable development—referred in this paper as the two Ss. While the four Cs were identified by the associates of the American Management Association based on the needs of the society, professional associations, and businesses; this paper proposes the two S extension to ensure that future engineers contribute to the well-being of individuals and the preservation of life on Earth. It proposes a tangible framework—the 4C2S—and an application method to analyse the contributions made by engineering capstone programmes to the development of these core competencies in future engineering professionals. The method is applied to an engineering capstone programme—the European Project Semester (EPS) offered by the Instituto Superior de Engenharia do Porto (ISEP)—and a specific project case—EPS@ISEP Pet Tracker project developed in 2013, constituting, in addition, a road map for the application of the 4C2S framework to engineering capstone programmes. The results show that EPS@ISEP complies with the 4C2S framework.